LOCAL COMMUNITY ASSEMBLIES IN SERBIA AS A FORM OF DIRECT CITIZEN PARTICIPATION IN LOCAL GOVERNMENT – BETWEEN TRADITION, REPRESENTATIVE AND DIRECT DEMOCRACY – - Radojević, Mijodrag; Matić, Petar (Serbian political thought, 2026)
The subject of this research is local community assemblies as forms of direct democracy in Serbia. The paper seeks to identify a correlation between the traditional forms of these assemblies and the development of local self-government and democracy. By using the doctrinal concepts of direct democracy and local self-government, as well as theoretical methods, such as the dogmatic and normative legal method, historical and comparative methods, and, based on empirical findings, the authors provide a diachronic overview of local assemblies of all citizens. These assemblies have a long tradition in Serbia. From former custom-based institutions, they were transformed into local government bodies during the nineteenth century. This transformation meant a gradual phasing-out of their direct representative character and their importance as central bodies of local government. The underlying cause of these changes results from the conflict between political conceptions of local democracy (decentralists) and proponents of a strong state and local administration (centralists), as well as broader political circumstances. The model of classical representative body in local self-government persisted until the beginning of World War II. In the post-war period, consistent with the ideological postulates of Marxism and self-management socialism, two new forms of these bodies emerged in the communist Yugoslavia – assemblies in local communities (citizens’ assemblies) and assemblies in business enterprises and organizations (working people’s assemblies). During the final decade of the twentieth century, following the dismantling of self-management socialism and a return to the classical model of local self-government, these forms of direct democracy at the local level were abolished. The authors conclude that the era of socialist self-management left a contradictory legacy in terms of attitudes toward direct democracy and direct citizen participation in local government. A residual element of such a legacy is the concept of assemblies in local communities, which, in practice, has no substantial role in the functioning of local self-government in Serbia. The authors point to the shortcomings in the legal framework and propose normative and technical solutions that could improve the way of citizens’ direct participation in the exercise of local power.